2016
DOI: 10.11002/kjfp.2016.23.2.246
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant abilities and physiological properties ofdried Haw extracts prepared using different drying methods

Abstract: This study was performed to determine the effects of drying methods (HD, hot air drying; FD, freeze-drying) on the antioxidant and physiological abilities of Haw (Crataegus pinnatifida Bunge). Powder color values of dried Haw, L and b, were higher for HD, while the chroma values were higher for FD. The total polyphenol, and flavonoid contents of HD Haw and FD Haw were found to be 9.29±0.50 mg GAE/mL and 15.48±0.38 mg GAE/mL, and 9.41±0.26 mg RHE/mL and 26.46±0.34 mg RHE/mL, respectively. DPPH radical scavengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The samples dried in a microwave appeared to have the highest antioxidant capacity and it was concluded that it was the best method for preserving bioactive phytochemicals (Saadatian et al, 2016). Freeze-drying was reported to be better than hot air drying for hawthorn (C. pinnatifida) in terms of antioxidant, α-glucosidase inhibitory potential, the TPC/TFC values and color (Kwon, 2016).…”
Section: Processing Quality Control and Other Usesmentioning
confidence: 99%
“…The samples dried in a microwave appeared to have the highest antioxidant capacity and it was concluded that it was the best method for preserving bioactive phytochemicals (Saadatian et al, 2016). Freeze-drying was reported to be better than hot air drying for hawthorn (C. pinnatifida) in terms of antioxidant, α-glucosidase inhibitory potential, the TPC/TFC values and color (Kwon, 2016).…”
Section: Processing Quality Control and Other Usesmentioning
confidence: 99%